Analysis of the Use and Reporting of BOSS Funds at LP MI Mamba'ul Hikmah Girimoyo, Karangploso Malang - Charisma Firdnandya Putri; Irfan Fatoni; Dwi Anggarani; Indah Dewi Nurhayati (Optima Science, 2024)
This study aims to determine the suitability of the receipt and use of a fund / asset from the applicable rules and regulations. This analysis includes data collection, data reduction, data validity, data presentation, data analysis, and conclusions. This research uses qualitative descriptive method with descriptive analytical approach case study. Data collection techniques are carried out by observation, interviews, and documentation. The data analysis technique used is the technique of analyzing the source and use of funds. The results of the study can be stated that, the use of BOS Funds by LP MI Mamba'ul Hikmah Girimoyo is in accordance with the rules and regulations of the Technical Directive (Juknis) of Permendikbudristek No.63 of 2022, but has not and/or has not fully implemented the 12 (twelve) components of the regulation. Because, the regulation does not require to carry out all the components listed. Likewise, the Reporting on the Use of BOS Funds is in accordance with the Reporting based on the Technical Guidelines (Juknis) of Permendikbudristek No. 63 of 2022. However, reporting based on Public Sector Accounting Reporting Standards has not been fully implemented. Evidenced by the existence of Financial Statements which include; Budget Realization Report (LRA), Cash Flow Statement, Operational Report and Excess Budget Balance Report (SAL). This is not a problem, because the reporting is in accordance with the Reporting based on the Technical Guidelines (Juknis) of Permendikbudristek No.63 of 2022.